Vertical Differentiation With A Positional Good - Luca Lambertini; Raimondello Orsi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
We investigate the role of positional effects in a market for vertically differentiated goods. We consider the two alternative settings, a single-product monopoly and a single-product duopoly. We evaluate the performance of both regimes against social planning. Contrary to conventional wisdom, we establish that it can be socially inefficient to expand the product range.
Keywords: 330